STUDI KASUS POLA ASUH ORANGTUA DAN KEMANDIRIAN ANAK TUNAGRAHITA DI SDN BENDO TRETEK 1 - Dwi pratiwi, Yunita; Rezania, Vanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the parenting patterns of parents of children with intellectual disabilities. This research uses a qualitative case study method and data collection techniques using observation, interviews, documentation and field notes. The research results show that a mentally retarded child is someone who experiences mental limitations or intelligence that is below average and has difficulty in being independent and socializing with the surrounding environment. Parents of children with intellectual disabilities use democratic parenting methods to help children become independent. Parents with intellectual disabilities can apply it to their children to see the conditions and limitations of each child. Keywords: independence of children, mental retardation, parents